Pengaruh Media Diorama Terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas III di Sekolah Dasar - Wardoyo, Sugeng; Armariena, Dian Nuzulia; Prasrihamni, Mega (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to describe the effect of diorama media on learning outcomes ofclass III language materials in elementary schools. That is how to develop diorama media in Indonesian language learning at SDN 234 Palembang in the academic year 2020/2021, thisresearch method is a type of experimental research. with pre-experimental designs (nondesigns). This experimental form was chosen because the form of this research design was in accordance with the sampling technique carried out by the researcher, which only involved one class as an experimental class or trial class with the aim of knowing the description of the effect of diorama media on learning outcomes of Indonesian language objects around me in class students. III sd. The technique of collecting data in this research uses documentation techniques and initial and final tests with learning materials, namely language texts that are taught to students. The results of the study showed that the average student learning outcomes increased from 69.2 or below the KKM to 75.0 or above the KKM. accepted or the hypothesis which states that